Design of a 1 DOF exoskeleton robotic system - Toh, Min Ruey. (2011)
It is very important for human to be able to carry out their daily activities. However, when someone is struck by a stroke, they are unable to perform the motion of their limbs smoothly or they probably are unable to move at all. This will obstruct them from living a normal lifestyle among others and it will be worst still if they are unable to support their family due to the incapability to perform their work. Medical robotic research is currently moving towards creating robotic actuators to help the stroke patients in their rehabilitation state by providing a more efficient and convenient way of exercise. The robot will increase the chances of recovery of stroke patients within a shorter period of time and without the observation of specialists.